COMPARING SEARCHING AND SORTING ALGORITHMS EFFICIENCY IN IMPLEMENTING COMPUTATIONAL EXPERIMENT IN PROGRAMMING ENVIRONMENT - Sagan, R. (Journal of Information Technologies in Education (ITE), 2011)
This article considers different aspects which allow defining correctness of choosing sorting algorithms. Also some algorithms, needed for computational experiments for certain class of programs, are compared.